Discrepancies between clinical and autopsy diagnosis of cause of death among psychiatric patients who died due to natural causes. A retrospective autopsy study - Mitrović, Dragan; Savić, Ivana; Janković, Radmila (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Autopsy studies rarely investigate the causes of natural death in psychiatric population. The aim of this study was to examine the causes of death among the subjects with various psychiatric disorders in whom a clinical (pathoanatomical) autopsy was requested. Methods. The study group included 118 patients (65% men, 35% women, mean age 58.2 ± 13.6 years) with a psychiatric diagnosis, in whom a clinical autopsy was performed. We compared the distribution of causes of natural death among psychiatric patients and other patients, representatives of the general population who died of natural causes. We also analyzed the difference between clinical diagnoses of cause of death and the autopsy findings in psychiatric patients. Results. Psychiatric patients died earlier than the control group (58 vs. 69 years), usually due to the respiratory (46%) and cardiovascular diseases (37%). The most common diagnoses in psychiatric patients were organic psychoses and dementias (F00-F09) and schizophrenia and schizoaffective disorders (F20-F29). Majority of the patients (55%) died in general hospitals vs. specialized psychiatric hospitals (45%) due to somatic diseases. There was a significant difference in the distribution of causes of death compared to the control group in which the cardiovascular diseases dominated. Even in 64% of psychiatric patients there was a discrepancy between the clinical diagnosis of the cause of death and definite autopsy findings. Conclusion. The assessment of somatic diseases in psychiatric patients is insufficient, especially in specialized psychiatric hospitals. That leads to a significant discrepancy between clinical diagnosis of the cause of death and autopsy findings. Therefore, it is necessary to pay additional attention in diagnostics and treatment of somatic diseases in these patients to improve their health care.
Keywords: autopsy; cause of death; death, sudden; diagnosis; hospitals, general; hospitals, psychiatric; mental disorders; patients